SATISFACTION LEVEL OF PATIENTS WITH SERVICES PROVIDED IN DENTAL OUTPATIENT DEPARTMENT OF RAWAL INSTITUTE OF HEALTH SCIENCES, ISLAMABAD - Abeera Faraz Abbasi,; Noman Noor,; Shazia Malik,; Muhammad Farooq Kamran, (Journal of Ayub Medical College Abbottabad, 2021)
Background: Patient satisfaction reflects the level of ease that the patient experiences having used a service. It can identify the gap between the actual experience of the services versus expected. Patients' satisfaction has been widely used in the lay measurement of quality of health service. The purpose of this study was to examine the structural relationships between out-patient satisfaction and service quality extent. Methods: This was a cross sectional study carried out on 196 conveniently selected patients from 5 July to 5 September 2018 at the general outpatient department of Rawal institute of Health sciences Islamabad. Parameters used to measure the satisfaction levels of the presenting patients were: ease of access, waiting time for the patients, patient-provider communication, patient-provider relationship, hospital administration, and general hospital ambiance and environment. Results: The overall satisfaction score of the patients under consideration was 74.48%. Specifically, the respondents were highly satisfied with due attention given by the doctors (80%). Around (74%) said that the presenting doctors addressed them with a very humble and polite attitude; 80% said that they would recommend this hospital to their contacts. While 56% of the patients said they had to wait for longer time for the doctor. Conclusion: This study reveals that the overall level of patients' satisfaction with the provided services was satisfactory. Patients were highly satisfied with attention given by the presenting doctors. The only major point for dissatisfaction was the waiting time and the explanation of the procedure